(3JSejW KdGK bUGFO ef bUGFO GHf GdNjGW GdOeTbis - (3eMeO Hf CMeO GdfMhi , GdedbH HGdQVGs; (3GHf GdNjGW , CMeO Hf eMeO Hf GdNjGW GdOeTbj, CHh YHO Gddg,J (B517 (3g` s
(3ChdgG (B:s
(3GdJSejW GdChd efgG (B:(3ddCOjH eMeO GdQVG GdMdHi SeW CHjGJ GHf GdNjGW GdOeTbi EPG faNJ CQhGM fLO hgVHg hgHJ UHGg gGL dGYL cQHg aHGddg jG Hfi hOg Ohf UMHg NPG ef UHG fLO CeGPG GdbdHg s
(3BNQgG (B:s
(3GdJSejW GdKGdK efgG (B: (3HOeYi QCJ aVd Gdhdi Ydi GdhSe hGdMeO ddg ChdG hBNQG hHGWfG hXGgQG hGdUdGI Ydi NjQ Ndbg eMeO hYdi Bdg hUMHg Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3GfXQg eY GdQSGdI GdMGJejIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JSejW TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs